The Influence of Price and Product Quality on Consumer Purchase Interest at the Surya Mas Rinda Accessories Store, Medan City Market Center - Cindy Mutiara; Zahara Meutia; Tri Auri Yanti (Harmony Management: International Journal of Management Science and Business, 2024)
The aim of this research is to see how price and product quality influence consumer buying interest at the Surya Mas Rinda Accessories Store which is located in the Medan City Market Center. The variables studied include price as (X1), product quality as (X2) and consumer purchasing interest as (Y). Data for this research was obtained through a survey with a sample of 77 people selected randomly. The technique used in this research uses multiple linear regression analysis with hypothesis testing, namely the t test and f test as well as the coefficient of determination using SPSS 26. The results of the t test show that price has no significant effect on consumer buying interest at the Surya Mas Rinda Accessories Shop, while product quality has a significant effect on consumer buying interest at the Surya Mas Rinda Accessories Store. The results of the f test show that price and product quality simultaneously influence consumer buying interest at the Surya Mas Rinda Accessories Store. The results of the coefficient of determination show that price and product quality influence consumer buying interest with a value of 37.7% and the remaining 62.3% is influenced by other variable factors outside this research. So it can be concluded that consumers are not sensitive to price as long as the product quality remains good.